Social Interaction With Agents and Avatars in Immersive Virtual Environments: A Survey - Kyrlitsias, Christos; Michael-Grigoriou, Despina (Frontiers in Virtual Reality, 2022)
Immersive virtual reality technologies are used in a wide range of fields such as training, education, health, and research. Many of these applications are including virtual humans which and are classified into avatars and agents. An overview of the applications and the advantages of immersive virtual reality and virtual humans is presented in this survey, as well as the basic concepts and terminology. In order to be effective, many virtual reality applications require that the users perceive and react socially to the virtual humans in a realistic manner. Numerous studies show that people can react socially to virtual humans, however, this is not always the case. This paper provides an overview of the main findings regarding the factors that affecting the social interaction with virtual humans within immersive virtual environments. Finally, this paper highlights the need for further research that can lead to better understanding of human-virtual human interaction.